2002
DOI: 10.1523/jneurosci.22-23-10346.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Netrin 1 ReceptorsUnc5h3andDccAre Necessary at Multiple Choice Points for the Guidance of Corticospinal Tract Axons

Abstract: Migrating axons require the correct presentation of guidance molecules, often at multiple choice points, to find their target. Netrin 1, a bifunctional cue involved in both attracting and repelling axons, is involved in many cell migration and axon pathfinding processes in the CNS. The netrin 1 receptor DCC and its Caenorhabditis elegans homolog UNC-40 have been implicated in directing the guidance of axons toward netrin sources, whereas the C. elegans UNC-6 receptor, UNC-5 is necessary for migrations away fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
166
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(188 citation statements)
references
References 42 publications
19
166
1
2
Order By: Relevance
“…Apoptosis in response to external survival cues may require a receptor, such as UNC5H1, and the presence of NRAGE to transmit the death signal. Once a cell has begun to differentiate, studies have shown that some neurons use UNC5Hs to mediate axon guidance or cell migration (3,7,11,34,35). Down-regulation of NRAGE would ensure that a differentiated neuron responding to guidance cues is no longer able to send an apoptotic signal through UNC5H1.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis in response to external survival cues may require a receptor, such as UNC5H1, and the presence of NRAGE to transmit the death signal. Once a cell has begun to differentiate, studies have shown that some neurons use UNC5Hs to mediate axon guidance or cell migration (3,7,11,34,35). Down-regulation of NRAGE would ensure that a differentiated neuron responding to guidance cues is no longer able to send an apoptotic signal through UNC5H1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Satb2 mutants show reduced expression of Unc5H3, a well-characterized axonal guidance receptor (9). In Unc5H3 mutants, subcerebral axons fail to descend past the decussation into the spinal cord (13), raising the possibility that Satb2 knockouts display a similar phenotype due to reduced expression of Unc5H3. An alternative possibility is that Satb2 may play a non-cell autonomous role in guiding subcerebral axons to the spinal cord.…”
Section: Visualization Of Callosal and Subcortical Axonal Connectionsmentioning
confidence: 99%
“…In particular, three axonal guidance molecules (EphA4, PlxnA4, and Unc5H3) are down-regulated in upper layers of mice lacking Satb2. Prior studies have implicated Ephs and ephrins in callosal development (13,28,29). EphA4 is normally expressed in upper layer callosal neurons and the glial wedge (28).…”
Section: Expression Of Epha4 and Unc5h3 Restores Callosal Projections Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in genes such as netrin1 (21), DCC and Unc5h3 (22), and slit1͞2 (23) cause defects in corpus callosum and pyramidal tract development; thus, we examined the expression of a variety of axon guidance molecules, including netrins and their receptors, Robo and slit family members, and semaphorins and plexins. Of 36 genes tested, no obvious differences in expression were detected at E14, E15, E17, or P0 ( Fig.…”
Section: Fezl Regulates the Expression Of Several Genes Expressed In mentioning
confidence: 99%